2020
DOI: 10.1029/2019wr025463
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Observation Data Uncertainty on Probabilistic Streamflow Forecasts Using a Dynamic Hierarchical Model

Abstract: Earlier researches have proposed algorithms to quantify the measurement uncertainty in rating curves and found that the magnitude of the uncertainty can be significant enough to impact hydrologic modeling. Therefore, they suggested frameworks to include measurement uncertainty in the rating curve to make it robust. Despite their efforts, a robust rating curve is often ignored in traditional practices, considering the investment of time and money as well as the resulting benefit from it. In the current research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…However, fitting the STHM purely for at-site would limit its ability to predict in ungauged predictions. In a traditional hierarchical modeling approach, this would be considered as an "unpooled regression" model (Das Bhowmik et al, 2020;Devineni et al, 2013) as such a model will result with no regional modeling terms. It can be easily understood that post-processing a model's flow would naturally result in improved model performance as regression is expected to reduce the model bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fitting the STHM purely for at-site would limit its ability to predict in ungauged predictions. In a traditional hierarchical modeling approach, this would be considered as an "unpooled regression" model (Das Bhowmik et al, 2020;Devineni et al, 2013) as such a model will result with no regional modeling terms. It can be easily understood that post-processing a model's flow would naturally result in improved model performance as regression is expected to reduce the model bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these two-step approaches have focused primarily on design flood as opposed to predicting daily flood flows, which are critically important for issuing early warnings. Further, these two-step regression modeling can be effectively integrated into a single step using a hierarchical model (Das Bhowmik et al, 2020;Devineni et al, 2013). To our knowledge, limited/no application of hierarchical model has been performed for estimating daily flows at ungauged locations over the CONUS.…”
Section: Introductionmentioning
confidence: 99%
“…This can be possible with the help of an understanding of measurement errors and pre-processing techniques employed. The estimation of measurement errors within the modeling framework will help to reduce these uncertainties (Das Bhowmik et al, 2020). The accuracy level of the measurement error does matter in in uencing the outcomes according to the employed modeling framework and type of measurement inputs.…”
Section: How Are Uncertainties Handled In Hydrological Forecasting?mentioning
confidence: 99%
“…A degradation in accuracy and availability can occur in modern sensory systems such as remote observation or complex IoT sensor networks and the usage of sensors. In such cases, any prior knowledge about measurement accuracy can be integrated into a qualitative /quantitative estimation of errors (Das Bhowmik et al, 2020). This knowledge of measurement error can help reduce measurement uncertainty, thereby, increasing the forecasts' reliability.…”
Section: Measurements and Inputsmentioning
confidence: 99%
“…This observed data was considered as the exact value and directly used in this paper. However, some researchers reported that the measurement errors of observation exist due to accidental factors (Bhowmik et al 2020). Therefore, the uncertainty from measurement errors in the reservoir operation may need to be considered in future studies.…”
Section: Limitations and Future Developmentsmentioning
confidence: 99%